Psychological Status of Healthcare Workers during the Covid-19 Pandemic - Yildirim, Tuba Talo; Atas, Osman; Asafov, Azad; Yildirim, Kadir; Balibey, Hakan (Coll Physicians & Surgeons Pakistan, 2020)
Objective: To assess the levels of health anxiety and Beck depression according to demographic variables among a sample of healthcare workers during the COVID-19 pandemic. Study Design: Cross-sectional, analytical study. Place and Duration of Study: Firat University and Medical Park Hosspital, Elazig, Turkey, from March to April 2020. Methodology: A total of 270 healthcare workers (100 males and 170 females) filled out health anxiety inventory (HAI), Beck depression inventory (BDI), questionnaires. Evaluations of HAI and BDI were conducted according to demographic variables (age, gender, marital status, jop, life style, smoking habits, sistemic disease). Results: Female healthcare workers had higher HAI and BDI scores than male (p <0.001, p <0.001). Young healthcare workers had higher HAI scores than aged healthcare workers (p=0.021) Healthcare workers with more knowledge about COVID-19 had lower HAI and BDI in (p=0.021, p=0.019). There is statistical significant differences in HAI and BDI scores in marital status (p = 0.022, p=0.002). The HAI and BDI scores of participants, who had close contact, were significantly higher than those who had no contact (p = 0.009 p=0.028). There were significant correlations between the two scales (p <0.05). Conclusion: During the COVID-19 pandemic, psychological support should be provided to all healthcare workers and working conditions should be corrected to relieve the anxiety and worry.
Keywords: COV1D-19; Healthcare workers; Health anxiety; Beck depress